2021
DOI: 10.11604/pamj.2021.40.209.30496
|View full text |Cite
|
Sign up to set email alerts
|

Management of chyle leak in right side neck dissection: a rare case and review of literature (a case report)

Abstract: Chyle leak is a well-recognized iatrogenic thoracic duct injury but a rare and serious complication of head and neck surgery affecting 1-2.5% of head and neck surgery dissections. It is potentially a life-threatening condition and management may be problematic and prolonged. Here we presented a rare case report of right sided chyle leak with its surgical management and review of literature. A 56-year-old patient with a complain of non-healing ulcer in the right buccal vestibule in the last 1-2 months reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Fifty-one reports were retrieved and assessed for eligibility. Finally, 40 articles were shortlisted and included in this review 7 - 46 . ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-one reports were retrieved and assessed for eligibility. Finally, 40 articles were shortlisted and included in this review 7 - 46 . ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the 40 studies, 139 patients were reported to have CL after head and neck surgeries (26 left neck dissections, 4 right neck dissections, 19 bilateral neck dissections, 85 neck dissections with side unspecified, and 6 patients who underwent other procedures of the neck such as lobectomy, thyroidectomy, or parathyroidectomy) 7 - 46 . ( Table 1 , Supplementary Table 1 )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation